Expression of Connexin 43 in the Porcine Foetal Gonads During Development. Issue 2 (2nd July 2012) - Knapczyk–Stwora, K; Durlej–Grzesiak, M; Duda, M; Slomczynska, M
Contents This study was designed to reveal connexin 43 (Cx43) mRNA and protein expression in porcine foetal gonads using RT‐PCR, immunohistochemistry and Western blot analysis. Expression of Cx43 was investigated in porcine foetal ovaries and testes on days 50, 70 and 90 post coitum (p.c.). RT‐PCR results indicated that Cx43 mRNA was expressed in both foetal ovaries and testes at all gestational ages examined. Cx43 protein was found in the foetal ovary but its distribution varied across ovarian compartments and changed during development. In foetal ovaries, Cx43 was localized between the interstitial cells surrounding egg nests on all investigated days of prenatal period. Moreover, Cx43 expression was observed between germ cells on day 50 p.c. as well as between pre‐granulosa and granulosa cells of primordial and primary follicles on days 70 and 90 p.c. In the foetal testes, Cx43 protein was detected between neighbouring Leydig cells on all examined days of prenatal period and between adjacent Sertoli cells exclusively on day 90 p.c. The presence of Cx43 protein in all investigated foetal gonads was confirmed by Western blot analysis. Cx43 protein detection between pre‐granulosa cells of primordial follicles suggests its role in regulation of the initial stages of follicle development. The Cx43 immunoexpression between neighbouring Leydig and between Sertoli cells indicates its involvement in controlling their functions. We propose that Cx43‐mediated gap junctional communication is involved in the regulation of porcine foetal gonadal development.